Implementasi Media Permainan Tingkatkan Motivasi dan Hasil Belajar IPAS Peserta Didik Kelas III - Rury Aisyaturida; Marista Dwi Rahmayantis; Ria Wahyuning Budiasri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to evaluate the use of educational games as a learning medium to enhance students' motivation and improve the quality of Natural and Social Sciences (IPAS) instruction at the elementary school level. The research employed a classroom action research approach consisting of two cycles. Data were collected through observations, documentation, assessment rubrics, tests, and field notes. The games used in the study included